Expansion of the range of meat products for special nutrition - Moskaluyk, Oksana; Haschuk, Olexandra; Kolomiets, Ilia (My University, 2025)
Healthy nutrition is one of the most important components of a healthy lifestyle, which, in turn, is the key to longevity, beauty and success in general. With food, the human body receives energy, micro and trace elements, vitamins necessary for the body. An important current trend in the organization of healthy nutrition is the use of various natural components in the composition of food products in order to increase their nutritional value. Given the increased content of antioxidants and tannins in the raw materials described above (dogwood, ginger, viburnum, sea buckthorn), it is advisable to study it with the possibility of using it in the technology of meat products, which allows you to expand the range, enrich the daily diet with useful nutrients that meet the physiological needs of the body and contribute to maintaining health, working capacity and active creative longevity of a person.
Keywords: кафедра технології м’яса і м’ясних продуктів; здорове харчування; природні компоненти; healthy eating; natural ingredients